2011
DOI: 10.1258/td.2011.110045
|View full text |Cite
|
Sign up to set email alerts
|

Reinforced tension line suture closure after midline laparotomy in emergency surgery

Abstract: Midline laparotomy is an emergency surgical operation frequently performed in cases of intra-abdominal pathology. Closure of the incision is usually done by continuous suturing by mass closure. In an emergency operation the intra-abdominal milieu is usually contaminated leading to gut oedema and, hence, an increase in postoperative intra-abdominal pressure. It is complicated by wound dehiscence, burst abdomen, etc. The cause of this complication is an increase in horizontal tensile forces on the site of the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 16 publications
1
8
0
Order By: Relevance
“…In 77% of the non‐reinforced sites, sutures tore away from the tissues at a median load of 60·7 N, which was a much lower force than tolerated by the reinforced sides. Similarly, Agarwal who used the RTL continuous technique in patients who underwent emergency midline laparotomies found that this technique resulted in no burst sutures. Furthermore, in 100 patients who were closed using a non‐RTL continuous suture wounds resulted in SWD ( P = 0·009).…”
Section: Resultsmentioning
confidence: 96%
“…In 77% of the non‐reinforced sites, sutures tore away from the tissues at a median load of 60·7 N, which was a much lower force than tolerated by the reinforced sides. Similarly, Agarwal who used the RTL continuous technique in patients who underwent emergency midline laparotomies found that this technique resulted in no burst sutures. Furthermore, in 100 patients who were closed using a non‐RTL continuous suture wounds resulted in SWD ( P = 0·009).…”
Section: Resultsmentioning
confidence: 96%
“…The PRISMA flow diagram of our additional search is shown in Addendum 3 (Key Question M). Eight records were screened by full text [78][79][80][81][82][83][84][85]. Three RCTs on the prevention of burst abdomen using either retention sutures or a reinforced tension line suture in patients with increased risk for wound dehiscence and burst abdomen were identified [78][79][80].…”
Section: Is There a Place For Retention Sutures When Closing A Laparomentioning
confidence: 99%
“…The Summary of Findings is listed in Table 4. Two studies showed favourable results [78,79], but one study reported a high number of adverse events when using retention sutures [80]. Hernia (2015) 19:1-24 11…”
Section: Is There a Place For Retention Sutures When Closing A Laparomentioning
confidence: 99%
“…If the risk of burst abdomen or postoperative large incisional hernia is considered to be high at abdominal closure, a longitudinal suture parallel to the fascial margin as a reinforced tension line may be used in combination with the standard continuous primary fascial closure suture along the fascia, in order to reduce the incidence of burst abdomen [36,37]. There is seldom a need to leave the patient with a giant planned ventral hernia, a condition associated with great morbidity and need for later advanced abdominal wall reconstruction.…”
Section: Discussionmentioning
confidence: 99%